RELATIONSHIP BETWEEN STUDENT’S IMAGINATION ABILITY AND CONCEPTION ON ATOMIC STRUCTURE CONCEPTS - Helda - (PROSIDING SEMINAR KIMIA, 2015)
Atomic orbital concept is a difficult subject for many high school and beginning undergraduate students, as it includes mathematical concepts not yet covered in the school curriculum. It requires certain ability for abstraction and imagination.The ability of imagination is one of mental model attributes affecting on student’s conception. This study aimed to identify imagination ability of student who had misconception and examine relationship between student’s imagination ability and conception in atomic structure concepts. The object of this research was 130 students of eleventh grade of SMAN Sumber rejo and SMAN Model Terpadu, Bojonegoro. Student’s misconception was determined based on the results of conceptual understanding (atomic structure) test. The student’s imagination ability was determined through the imagination diagnostic test that has been qualified in terms of validity and reliability. It was categorized into three levels, namely, high as level 1, moderate as level 2, low as level 3. The burden of student’s misconception was categorized into three levels involving low, middle, and high. Determining of it used central tendency (mean) and dispersion (standard deviation). There were three main result of this research. First, students who had misconception have varying abilities to imaginating in all levels (level 1 to level 3). Second, the average percentage of students who had misconception with low, middle, and high level of imagination abilityare 81.3, 76.7, and 47.9 % respectively. Third, based on the results of X2 analysis, it was obtained p-value 0.019, less than α = 0.05. It means that there was relation significantly between the level of student’s imagine ability and burden misconception level. Students having low imagine ability had the high possibility for possessing misconception in atomic structure concepts.